Dissection of Trichoderma longibrachiatum-induced defense in onion (Allium cepa L.) against Fusarium oxysporum f. sp. cepa by target metabolite profiling. (May 2016) - Abdelrahman, Mostafa; Abdel-Motaal, Fatma; El-Sayed, Magdi; Jogaiah, Sudisha; Shigyo, Masayoshi; Ito, Shin-ichi; Tran, Lam-Son Phan
Highlights: T. longibrachiatum confer beneficial traits and induce Fusarium defense to onion. Metabolite profiling was used to identify the associated pathways and mechanisms. Carbohydrate, flavonoid and sulfur assimilation metabolic pathways were upregulated. Accumulation of detected metabolites enhanced onion resistance to Fusarium . Abstract: Trichoderma spp. are versatile opportunistic plant symbionts that can cause substantial changes in the metabolism of host plants, thereby increasing plant growth and activating plant defense to various diseases. Target metabolite profiling approach was selected to demonstrate that Trichoderma longibrachiatum isolated from desert soil can confer beneficial agronomic traits to onion and induce defense mechanism against Fusarium oxysporum f. sp. cepa (FOC), through triggering a number of primary and secondary metabolite pathways. Onion seeds primed with Trichoderma T1 strain displayed early seedling emergence and enhanced growth compared with Trichoderma T2-treatment and untreated control. Therefore, T1 was selected for further investigations under greenhouse conditions, which revealed remarkable improvement in the onion bulb growth parameters and resistance against FOC. The metabolite platform of T1-primed onion (T1) and T1-primed onion challenged with FOC (T1 + FOC) displayed significant accumulation of 25 abiotic and biotic stress-responsive metabolites, representing carbohydrate, phenylpropanoid and sulfur assimilation metabolic pathways. In addition, T1- and T1 + FOC-treated onion plants showed discrete antioxidant capacity against 1, 1-diphenyl-2-picrylhydrazyl (DPPH) compared with control. Our findings demonstrated the contribution of T . longibrachiatum to the accumulation of key metabolites, which subsequently leads to the improvement of onion growth, as well as its resistance to oxidative stress and FOC.